2021
DOI: 10.17159/sajs.2021/7852
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and relative humidity trends in the northernmost region of South Africa, 1950–2016

Abstract: The northernmost Limpopo Province is located in one of the warmest regions of South Africa, where the agricultural sector is prone to heat stress. The aim of this study was to explore air temperature and relative humidity trends for the region, which have implications for agricultural adaptation and management (amongst other sectors). In particular, we investigated seasonal, annual and decadal scale air temperature and relative humidity changes for the period 1950–2016. Positive temperature trends were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(65 reference statements)
2
0
0
Order By: Relevance
“…Analysis of climatic patterns over 16 years in this study shows increasing average temperatures over the study period, which is consistent with published research within the region and contributes to the wider conversation surrounding climate change. Nyoni et al 24 reported a similar temperature trend (rate of + 0.02 °C/year) as observed in this study in parts of South Africa between 1950 and 2016. According to James and Washington 25 , majority of Africa warms faster than what is noted in other parts of the world.…”
Section: Discussionsupporting
confidence: 89%
“…Analysis of climatic patterns over 16 years in this study shows increasing average temperatures over the study period, which is consistent with published research within the region and contributes to the wider conversation surrounding climate change. Nyoni et al 24 reported a similar temperature trend (rate of + 0.02 °C/year) as observed in this study in parts of South Africa between 1950 and 2016. According to James and Washington 25 , majority of Africa warms faster than what is noted in other parts of the world.…”
Section: Discussionsupporting
confidence: 89%
“…of our findings and buttressed by numerous scholarly works of literature includingEngelbrecht et al (2015);Nyoni et al (2021);Carcel et al (2015). Consistent with our findings confirmed that South Africa's annual surface mean temperature has increased by 02°C to 0.06°C per annum in the past two decades.…”
supporting
confidence: 92%